2021
DOI: 10.1021/acs.jpcc.1c01618
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Coadsorption and Reactivity of O and CO on Ru(0001) and Their Coverage Dependence

Abstract: Using density functional theory and an exchange–correlation functional that includes the van der Waals interaction, we study the coadsorption of CO on Ru(0001) saturated with 0.5 ML of oxygen. Different coexisting CO coverages are considered that are experimentally motivated, the room temperature coverage consisting of 0.5 ML-O + 0.25 ML-CO (low coverage), the saturation coverage achieved at low temperatures (0.5 ML-O + 0.375 ML-CO, intermediate coverage), and the equally mixed monolayer that is stable accordi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 77 publications
5
30
0
Order By: Relevance
“…The fact that CO desorption dominates over CO oxidation is particularly striking considering that previous DFT calculations of the minimum energy reaction paths showed that desorption requires around 0.38 eV of additional energy compared to oxidation at this coverage. 4 The natural question that arises is whether the laser-induced oxidation dynamics does or does not proceed through that minimum energy oxidation path, in which the less bound O fcc abandons its adsorption well, crosses the bridge site between two Ru atoms, and recombines with the nearby CO that tilts to form the chemisorbed bent CO 2 (hereafter denoted bCO 2 ). The selected snapshots depicted in Figure 2 for one of the trajectories confirm that this is the case.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The fact that CO desorption dominates over CO oxidation is particularly striking considering that previous DFT calculations of the minimum energy reaction paths showed that desorption requires around 0.38 eV of additional energy compared to oxidation at this coverage. 4 The natural question that arises is whether the laser-induced oxidation dynamics does or does not proceed through that minimum energy oxidation path, in which the less bound O fcc abandons its adsorption well, crosses the bridge site between two Ru atoms, and recombines with the nearby CO that tilts to form the chemisorbed bent CO 2 (hereafter denoted bCO 2 ). The selected snapshots depicted in Figure 2 for one of the trajectories confirm that this is the case.…”
mentioning
confidence: 99%
“…6,19,[22][23][24][25][26] All (T e , T l )-AIMDEF simulations are performed with vasp 27,28 and the AIMDEF module 19,[29][30][31][32][33][34] using the same computational parameters and the same van der Waals exchange-correlation functional by Dion et al 35 that were used in our previous structural study. 4 Electronic friction coefficients are calculated with the local density friction approximation (LDFA). 36,37 The O K-edge XAS have been obtained with the transition potential and ∆-Kohn-Sham methods as implemented in GPAW.…”
mentioning
confidence: 99%
See 3 more Smart Citations